2012
DOI: 10.4103/2230-8598.107358
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of QOL and its determining factors of post menopausal women in a rural area of West Bengal, India: A multivariate analysis

Abstract: The aim was to assess QOL and its determining factors among postmenopausal women of a rural area of West-Bengal in India. Methods: This cross-sectional study was conducted among 315 postmenopausal women and the data were collected using the modified menopause quality of life questionnaire of Hilditch. (Hilditch MENQOL). Results: Out of the 315 women who have been interviewed 243 (77%) had poor quality of life. Multivariate analysis revealed that poor QOL was more among those who did not live with their own chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…15 A study by Ray et al in Kolkata found 77% of the women having poor quality of life. 5 Multivariate analysis revealed that poor QOL was more among those who did not live with their own children, were monetarily dependent on their children, not living under one roof with children and had attained menopause more than 5 years. This was in accordance with the present study, where the relationship between symptoms as per MENQOL domains and monetary autonomy of menopausal women in family showed a significant difference of mean between those who had monetary autonomy in their family and those who did not have any monetary autonomy in the family, with respect to the prevalence of Physical symptoms among them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 A study by Ray et al in Kolkata found 77% of the women having poor quality of life. 5 Multivariate analysis revealed that poor QOL was more among those who did not live with their own children, were monetarily dependent on their children, not living under one roof with children and had attained menopause more than 5 years. This was in accordance with the present study, where the relationship between symptoms as per MENQOL domains and monetary autonomy of menopausal women in family showed a significant difference of mean between those who had monetary autonomy in their family and those who did not have any monetary autonomy in the family, with respect to the prevalence of Physical symptoms among them.…”
Section: Discussionmentioning
confidence: 99%
“…The duration, severity, and impact of these symptoms vary extremely from person to person, and population to population. 5 Some women have severe symptoms that greatly affect their personal and social functioning quality of life. Vasomotor symptoms are common physical conditions experienced by midlife women in the transition through menopause and early post menopause.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the goals of health service for all the people in 21 st century is to improve quality of life. By WHO definition, quality-of-life is the individual's perception of their status in life according to the culture and value systems the person lives in, considering his goals, expectations, standards and concerns [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 With the increasing life expectancy, a woman spends one third of her life in menopause. 2 Menopause can have psychological, physical, and vasomotor symptoms along with sexual dysfunction. Nearly, 50 to 80% of women complain of menopausal symptoms such as hot flushing, sweating, sleep disturbance tiredness, and depression.…”
Section: Introductionmentioning
confidence: 99%